IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN GEOGRAFI DI SMA PEMBANGUNAN LAB UNP - Dewi Sugianti; Khairani Khairani (JURNAL BUANA, 2020)
This research aims to determine learning devices, learning processes and learning assessments using the implementation of curriculum 2013. This type of research is qualitative descriptive research. Data collection techniques through, observation, interviews and documentation. Data analysis techniques use analysis methods during the field of Model Miles and Huberman. The results of this study indicate that the geographical learning device is already in accordance with the instructions for Candy No. 103 year 2014, there are only a few additional elements and there are still some elements that have not been in order. Geography Learning activities using the curriculum 2013 is already running well. The teacher's learning evaluation is in accordance with the 2013 curriculum, which is the assessment of attitudes, knowledge and skills.